Why Do Bureaucrats Make Campaign Contributions to Presidential Candidates?: Evidence from 2004 to 2012. Issue 4 (12th November 2018) - Limbocker, Scott
Abstract : Like other citizens, federal employees commit time and money to presidential candidates seeking federal office. However, unlike other citizens, federal employees work in an executive establishment governed by a person to whom they may donate. Are the contributions the collective will of the agency or an incorrect aggregation of individual action? By merging two original surveys of federal employees with all Federal Election Commission records of individual donations, this study examines the contribution behavior of federal employees to presidential candidates in 2004, 2008, and 2012. I find that the rate at which federal employees contribute to presidential candidates varies depending on the bureaucrat's political beliefs, characteristics about the job the individual performs, and career values of the individual federal employee. I find little evidence that contributions vary systematically from agency‐wide characteristics.